Forever Suspect : Racialized Surveillance of Muslim Americans in the War on Terror - Selod, Saher, 1973- (Book collections on Project MUSE., 2018)
"The declaration of a "War on Terror" in the aftermath of the September 11, 2001 terrorist attacks brought sweeping changes to the American criminal justice and national security systems, as well as a massive shift in the American public opinion of both individual Muslims and the Islamic religion generally. Since that time, sociologist Saher Selod argues, Muslim Americans have experienced higher levels of racism in their everyday lives. In Forever Suspect, Selod shows how a specific American religious identity has acquired racial meanings, resulting in the hyper surveillance of Muslim citizens. Drawing on forty-eight in-depth interviews with South Asian and Arab Muslim Americans, she investigates how Muslim Americans are subjected to racialized surveillance in both an institutional context by the state and a social context by their neighbors and co-workers. Forever Suspect underscores how this newly racialized religious identity changes the social location of Arabs and South Asians on the racial hierarchy further away from whiteness and compromises their status as American citizens."--